2004
DOI: 10.1007/s00284-004-4303-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exopolymer-Producing Bacterium, Paracoccus zeaxanthinifaciens subsp. payriae, Isolated from a ?Kopara? Mat Located in Rangiroa, an Atoll of French Polynesia

Abstract: An aerobic, mesophilic and heterotrophic marine bacterium designated RA19, able to produce two different exocellular polymers and zeaxanthin, was isolated from a French polynesian bacterial mat (localy named "kopara") situated in the atoll of Rangiroa. This microorganism, on the basis of its phenotypical features and the genotypic investigations, can be clearly assigned to the Parococcus zeaxanthinifaciens species and the name Parococcus zeaxanthinifaciens subsp. payriae is proposed. Optimal growth occurs betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Enrichment cultures were purified on marine agar 2216E (MA, Difco Laboratories, Detroit, MI). Strain RA19 was selected because of its ability to exhibit a swarming mucoid phenotype on marine agar 2216E supplemented with 30 g l -1 of glucose along with a pigment further identified as pure all-trans-zeaxanthin [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enrichment cultures were purified on marine agar 2216E (MA, Difco Laboratories, Detroit, MI). Strain RA19 was selected because of its ability to exhibit a swarming mucoid phenotype on marine agar 2216E supplemented with 30 g l -1 of glucose along with a pigment further identified as pure all-trans-zeaxanthin [19].…”
Section: Methodsmentioning
confidence: 99%
“…This strain, P. zeaxanthinifaciens subsp. payriae, has been deposited in the Collection Nationale de Culture de Microorganismes (Institut Pasteur, Paris, France) as strain CNCM I-2926 [19]. The crude chemical composition included approximately 48% (w/w) neutral sugars, 8% (w/w) uronic acid, 8% (w/w) acetate and 27% (w/w) sulphate [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular water loss imposes a series of structural, physiologic, and biochemical challenges that microbes must overcome in order to survive. Several studies have suggested that for microorganisms found in extreme environments exposed to hypersalinity, desiccation and UV radiation are capable of producing large amounts of extracellular exopolymers (62,67). Extracellular polymers enhance biofilm formation and may be major components of the water loss VOL.…”
Section: Survival Systems For Environmental Stress: the Relationship mentioning
confidence: 99%
“…In November 2001, many samples of 'kopara' were collected from the different microbial mats located on the atoll of Rangiroa (Raguénès et al 2004). Enrichment cultures were purified on Marine Agar 2216E (Difco Laboratories, Detroit, MI, USA).…”
Section: Bacterial Strainmentioning
confidence: 99%